Kepemimpinan Transformasional Kepala Sekolah Dalam Mengembangkan Kompetensi Profesional Guru Di SD Islam Al Muttaqin Kota Sawahlunto - Nurmaningsih Yani; Ridwal Trisoni; Devy Aisyah; Jamilus Jamilus; Elda Herlina (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study analyzes how transformational leadership practiced by the principal contributes to the development of teachers' professional competence at SD Islam Al Muttaqin Sawahlunto. The study employed a qualitative case-study design because it sought to understand leadership practices in their natural school context. Data were collected through in-depth interviews, direct observation, and document analysis involving the principal, teachers, and a school mentoring stakeholder selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model through data condensation, coding, categorization, theme construction, data display, and conclusion drawing. The findings show that the principal developed teachers' professional competence through four interrelated transformational leadership practices: idealized influence was reflected in role modeling, discipline, and consistency in school values; inspirational motivation appeared in the strengthening of a shared vision and collective work commitment; intellectual stimulation was shown through teacher reflection forums, learning innovation, and the use of digital media; and individualized consideration was realized through personal mentoring, differentiated coaching, and support for teacher professional development. The study contributes a contextual model of transformational leadership in an Islamic elementary school, showing that professional competence develops more effectively when leadership combines exemplary conduct, collaborative motivation, reflective innovation, and personal assistance. These findings imply that principals need to act not only as administrators but also as learning leaders who build a sustainable professional culture among teachers.